2015
DOI: 10.4108/eai.14-10-2015.2261619
|View full text |Cite
|
Sign up to set email alerts
|

A Cascade-Classifier Approach for Fall Detection

Abstract: The current machine learning algorithms in fall detection, especially those that use a sliding window, have a high computational cost because they need to compute the features from almost all samples. This computation causes energy drain and means that the associated wearable devices require frequent recharging, making them less usable. This study proposes a cascade approach that reduces the computational cost of the fall detection classifier. To examine this approach, accelerometer data from 48 subjects perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Although Ojetola improved the detection rate, our prior work [ 14 ] showed that the method has a high computational cost because it has to extract features for every possible segment produced by the sliding window. A cascade-classifier approach (CCA) was developed to reduce this cost, and it also improved the classification performance.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Although Ojetola improved the detection rate, our prior work [ 14 ] showed that the method has a high computational cost because it has to extract features for every possible segment produced by the sliding window. A cascade-classifier approach (CCA) was developed to reduce this cost, and it also improved the classification performance.…”
Section: Related Workmentioning
confidence: 99%
“…Threshold-based approaches detect falls by checking if the measured acceleration exceeds a predefined (and fixed) value [ 6 , 7 , 8 ]. Machine learning-based approaches use labeled data to train a classifier using supervised machine learning algorithms (e.g., the support vector machine (SVM), decision tree, and/or artificial neural networks) that can recognize the characteristic features of falls [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations